Pengaruh Tingkat Pendidikan, Motivasi dan Pengalaman Kerja Terhadap Kinerja Perangkat Desa di Kecamatan Pagerageung Kabupaten Tasikmalaya - Sani Haryati; Siti Amirah Makarim (CV. Multi Kreasi Media, 2023)
The purpose of this study was to analyze the effect of education level, motivation and work experience towards employees’ performance of village apparatus in Pagerageung District, Tasikmalaya Regency, both partially and simultaneously. The sample of this study were 100 village apparatus in Pagerageung District, Tasikmalaya Regency and were chosen by using total sampling technique (sampling saturated). The data used were primary and secondary data. According to the process of data, multiple linear regression was used in this present study. The results showed that the coefficient determination (R2) were in score of 0.520, which means that the variables of Education Level (X1), Work Experience (X2) and Motivation (X3) towards Village Apparatus Performance variable (Y) categorized as a low relationship. Then, the value of R square was obtained 0.270 which means the effect of Level of Education (X1), Work Experience (X2) and Motivation (X3) towards Village Apparatus Performance (Y) was obtained score of 27% while the remaining 63% is influenced by other variables which is not analyzed in this study.